2018
DOI: 10.1159/000488630
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Attenuates Neurogenetic Damage and Improves Neurocongnitive Deficits Induced by Isoflurane in Neonatal Rats

Abstract: Background/Aims: Isoflurane inhibited neurogenesis and induced subsequent neurocognitive deficits in developing brain. Simvastatin exerts neuroprotection in a wide range of brain injury models. In the present study, we investigated whether simvastatin could attenuate neurogenetic inhibition and cognitive deficits induced by isoflurane exposure in neonatal rats. Methods: Sprague-Dawley rats at postnatal day (PND) 7 and neural stem cells (NSCs) were treated with either gas mixture, isoflurane, or simvastatin 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…However, there is still lack of data on isoflurane-induced NSC injury. In the present study, we showed that isoflurane exposure (3.4%, 6 h) inhibited neurogenesis by decreasing NSC proliferation and viability as well as increasing NSC apoptosis, which is consistent with the previous studies 28,29) . Additional, we also demonstrated that 3 consecutive day's isoflurane exposure on neonatal mice induced late cognitive deficits in adult, which supported the previous studies [11][12][13][14][15] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, there is still lack of data on isoflurane-induced NSC injury. In the present study, we showed that isoflurane exposure (3.4%, 6 h) inhibited neurogenesis by decreasing NSC proliferation and viability as well as increasing NSC apoptosis, which is consistent with the previous studies 28,29) . Additional, we also demonstrated that 3 consecutive day's isoflurane exposure on neonatal mice induced late cognitive deficits in adult, which supported the previous studies [11][12][13][14][15] .…”
Section: Discussionsupporting
confidence: 93%
“…As a main anabolism pathway in cellular signal transduction, Akt/GSK-3β signaling pathway plays an importantly mediated role in cell survival, proliferation, apoptosis and metabolism 36) . Akt/GSK-3β pathway is involved in isoflurane-induced neurogenesis inhibition and cognitive impairment 28) . There are also similar studies on other anesthetics such sevoflurane and ketamine 27,37,38) .…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoflurane is an isomeride of enflurane, which was commonly used in inhalation anesthesia. But, isoflurane can induce neurogenetic damage and neurocognitive disorder, even accelerate the process of Alzheimer's disease [17][18][19].With a view to the adverse effects of inhalational anesthetic compare to intravenous anesthetic. EIso was manufactured by West China Hospital of Sichuan University, which liquid isoflurane was mixed with intralipid at the final concentration of 8% (v/v).…”
Section: Discussionmentioning
confidence: 99%
“…At P57, rats were subjected to fear conditioning test as described previously (Wang et al., 2018). Briefly, the test was composed of two days.…”
Section: Methodsmentioning
confidence: 99%